Technology and diversity in higher education new challenges - Inoue, Yukiko (Information Science Publishing, 2007)
"This book examines current and effective educational practices as well as new challenges involving emerging technologies in increasingly diverse learning environments in higher educationand the impact of the explosion of technology. These challenges are well documented in this collection of essays, case studies, and research reports"
Includes bibliographical references and index
Keywords: Education, Higher -- Computer-assisted instruction; Educational technology; Medienpädagogik; Hochschule; Aufsatzsammlung